Teacher Perceptions of School Climate During the Transition to a Middle School Configuration - Robinette, Misty (My University, 2016)
The impact that a year of dynamic changes, including the transition to a middle school configuration, had on the perceptions of teachers about the overall climate of the school was examined in a qualitative case study. Interviews and observations were employed to gather information about the changing attitudes of faculty members as they faced new challenges that came along with the new school. Observations were used to solidify the interviewees' responses. The year of transition was marked by a steady decline in staff morale and a negative perception of school climate by the majority of teachers. Although there were hosts of contributing factors, based on the data, the primary reasons for the poor climate originated at the school level. These problems included poor administrative support and communication and a general lack of trust among teachers and administrators when making decisions for the welfare of the school. The primary finding was a distinct need for school leaders to reevaluate the ways they interact with the teaching staff. Recommendations include being more visible and accessible, cutting down on unnecessary reassignments, recognizing ideas and good teaching practices, communicating openly, and reinstating the team teaching approach to foster relationships and enhance teaching abilities.
I. INTRODUCTION 1 | Statement of the Problem 4 | Purpose of the Study 4 | Research Questions 5 | Significance of the Study 5 | Definition of Terms 6 | II. REVIEW OF LITERATURE 8 | School Climate 8 | The Middle School Design 18 | Rural Schools 23 | Race to the Top 26 | Common Core and New State Standardized Tests 28 | Teacher Evaluations 32 | Focus School Status 36 | III. METHODS 38 | Theoretical Framework 38 | Overview of Procedures 41 | Setting 42 | Participants 46 | Possible Types and Sources of Information or Data 47 | Data Analysis 49 | Validity 52 | Limitations of the Study 53 | Ethical Concerns 56 | Summary 57 | IV. FINDINGS 59 | Participant Profiles 60 | Analytic Approach 73 | Data Analysis 73 | Coding 74 | Validity, Trustworthiness, and Reliability 76 | Research Question 1 Results 76 | Research Question 2 Results 82 | Research Question 3 Results 94 | Summary...................................................................................99 | V. DISCUSSION AND RECOMMENDATIONS 101 | Summary of Research 101 | Research Question 1 104 | Research Question 2 115 | Research Question 3 121 | Recommendations 128 | Conclusion 134 | A Final Note 137 | | REFERENCES 139 | APPENDIX A: Initial Interview Questions 156 | APPENDIX B: Sample Field Observation Report 159 | APPENDIX C: Institutional Review Board Exemption Form 161 |
Keywords: Dissertation; Curriculum and Instruction